2021
DOI: 10.3390/ani11061519
|View full text |Cite
|
Sign up to set email alerts
|

Live Bacillus subtilis natto Promotes Rumen Fermentation by Modulating Rumen Microbiota In Vitro

Abstract: Previous studies have shown that Bacillus subtilis natto affects rumen fermentation and rumen microbial community structure, which are limited to detect a few microbial abundances using traditional methods. However, the regulation of B. subtilis natto on rumen microorganisms and the mechanisms of microbiota that affect rumen fermentation is still unclear. This study explored the effects of live and autoclaved B. subtilis natto on ruminal microbial composition and diversity in vitro using 16S rRNA gene sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
3
7
0
Order By: Relevance
“…The normal range for rumen fluid is 5.50 to 7.50, too high pH will affect the absorption of VFA by the rumen epithelium, while too low pH is not conducive to the feed fermentation in the rumen (Padilla, 2022). Similar result to Deng et al (2018) research, we found MIP decreased the rumen pH, however, Chang et al (2021) research result was quite the opposite (Deng et al, 2018;Chang et al, 2021), the addition of yeast cultures to high-concentration diet could enhance the pH value of rumen fluid and his result was consistent with Thrune et al (2009) and Dias et al (2018) works (Thrune et al, 2009;Dias et al, 2018).…”
Section: Rumen Fermentationsupporting
confidence: 79%
“…The normal range for rumen fluid is 5.50 to 7.50, too high pH will affect the absorption of VFA by the rumen epithelium, while too low pH is not conducive to the feed fermentation in the rumen (Padilla, 2022). Similar result to Deng et al (2018) research, we found MIP decreased the rumen pH, however, Chang et al (2021) research result was quite the opposite (Deng et al, 2018;Chang et al, 2021), the addition of yeast cultures to high-concentration diet could enhance the pH value of rumen fluid and his result was consistent with Thrune et al (2009) and Dias et al (2018) works (Thrune et al, 2009;Dias et al, 2018).…”
Section: Rumen Fermentationsupporting
confidence: 79%
“…Besides, probiotics could simultaneously affect the rumen fermentation and rumen microbial community structure to improve the digestive metabolism. For instance, the activity of Bacillus subtilis natto reportedly improved the concentrations of ammonia nitrogen, microbial protein and volatile fatty acids (VFA) in rumen fluid connected to the change in 18 genera of rumen fluid ( Chang et al, 2021 ).…”
Section: Impact Of Probiotic Microorganisms On Animals’ Welfarementioning
confidence: 99%
“…B. subtilis natto is shown to improve animal production and meat quality, with studies indicating that B. subtilis natto N21 in combination with lactic acid bacteria enhances broiler growth performance, feed conversion ratio, and nutrient digestibility [ 11 ]. Cows fed B. subtilis natto exhibit increased milk production, improved rumen fermentation, and a positive effect on the ruminal microbiome [ 12 ], while B. subtilis natto also promotes rumen fermentation by modulating rumen microbiota in vitro [ 13 ]. In TOPIGS pigs, B. subtilis natto supplementation resulted in a decrease in skatole content and an increase in meat tenderness [ 14 ].…”
Section: Introductionmentioning
confidence: 99%